Effects of silica gel on reduction in gluten during several beer brewing stages - Benitez, Elisa Ines (2016)
Beer is an alcoholic beverage made with barley as a basic raw material, and therefore, it is not suitablefor people with coeliac disease. During the brewing process, the elimination of the haze-active precursoris performed at the stabilisation stage. Some breweries use silica gel (SG) as stabilisation precursor. Thiswork presents the studies conducted to identify the stage where the addition of SG is more convenient inorder to reduce gluten, and the effect on the yeast nutritional value due its incorporation. The incorporationof SG during fermentation allows the reduction in more gluten than the others brewery stages studied,without changing significantly the yeast nutritional value of beer. Furthermore, the use of SGpromotes the reduction in polysaccharides which obstruct filtration.